How To Teach Knot Tying: A Kinesthetic Approach - Edward Hyung Kim; Hueylan Chern; Emily Huang; Barnard Palmer (Association of American Medical Colleges, 2013)
Abstract Introduction The purpose of this resource is to introduce surgical instructors to a better way of teaching the basic surgical skill of knot tying and to provide quality materials for trainees to use as they learn to tie surgical knots. Instructors using this educational resource will better understand why kinesthetics (the proper manipulation of suture) are important to the process of knot tying and then be able to apply this understanding when they teach the basic knot-tying curriculum. Methods The resource includes an instructor's manual discussing key kinesthetic aspects of surgical knot tying and a set of six skills exercises designed to help trainees practice to become proficient at tying surgical knots. Also included are a process-based evaluation tool that accompanies each exercise and an instructional video demonstrating the key kinesthetic concepts that should be taught at each step. Results In a pilot study undertaken at our skills lab, we randomized 17 first-year medical students without prior surgical experience into groups utilizing American College of Surgeons (ACS) or kinesthetic instruction models. After 1 week of practice, we videotaped students performing 6 two-handed square knots; then, four experienced surgeons scored the deidentified videos. Students returned their practice knots, and the lengths of these knots were measured as an indicator of practice to assess for confounding. We found that the kinesthetic group scored significantly higher than the ACS group, with no significant difference in the amount of practice between the two groups. Discussion This was a relatively small and short study, but the significant difference after a relatively short amount of practice time is both expected and very promising.